Comparison of Robotic and laparoscopic Radical type-B and C hysterectomy for cervical cancer: Long term-outcomes. - Pellegrino, Antonio; damiani, gianluca raffaello; Loverro, Matteo; Pirovano, Cecilia; Fachechi, Giorgio; Corso, Silvia; Trojano, Giuseppe (Acta Biomedica Atenei Parmensis, 2017)
Study Objective: To compare the clinical and oncologic outcomes of Robotic radical hysterectomy (RRH) vs Laparoscopic radical hysterectomy (TLRH) in patients with cervical carcinoma. Design: Long term follow-up in a prospective study between March 2010 to March 2016. Setting: Oncological referral center, department of gynecology and obstetrics of Alessandro Manzoni Hospital, department of gynecology, University of San Gerardo Monza, Milan. Patients: 52 patients with cervical carcinoma, matched by age, body mass index, tumor size, International Federation of Gynecology and Obstetrics (FIGO) stage, comorbidity, previous neoadjuvant chemotherapy, histology type, and tumor grade to obtain homogeneous samples. Interventions: Patients with FIGO stage IA2 or IB1 with a tumor size less than or equal to 2 cm underwent RR type B. RR-Type C1 was performed in stage IB1, with a tumor size larger than 2 cm, or in patients previously treated with NACT (IB2). In all cases Pelvic lymphadenectomy was performed for the treatment of cervical cancer. Measurements and main results: Surgical time was similar for both the 2 groups. RRH was associated with significantly less (EBL) estimated blood loss (P=0,000). Median number pelvic lymph nodes was similar, but a major number of nodes was observed in RRH group (35.58 vs 24.23; P=0,050). The overall median length of follow-up was 59 months (range: 9-92) and 30 months (range: 90-6) for RRH and TLRH group respectively. Overall survival rate (OSR) was 100% for RRH group and 83.4% for LTRH group. The DFS (disease free survival rate) was of 97% and 89% in RRH and LTRH group respectively. No significant difference was reported in HS (hospital stay). Conclusions: RRH is safe and feasible and is associated with an improved intraoperative results and clinical oncological outcomes. The present study showed that robotic surgery, in comparison to laparoscopic approach, was associated with better perioperative outcomes because of a decrease of EBL, and similar operative time, HS and complication rate, without neglecting the long-term optimal oncologic outcomes.